When Winning Is Losing: Why the Nation that Invented the Computer Lost Its Lead. - Hicks, Marie (Computer (00189162), 2018)
The nation that invented the computer lost its lead by discarding its most plentiful supply of trained technologists: women. This article discusses why failure narratives are as important to understanding the history of computing as success stories, and explains how structural sexism has affected the progress of computing.